2022
DOI: 10.20944/preprints202207.0396.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymmetry in Galaxy Spin Directions -- Analysis of Data from DES and Comparison to Four Other Sky Surveys

Abstract: The paper shows an analysis of the large-scale distribution of galaxy spin directions of 739,286 galaxies imaged by DES. The distribution of the spin directions of the galaxies exhibits a large-scale dipole axis. Comparison of the location of the dipole axis to a similar analysis with data from SDSS, Pan-STARRS, and DESI Legacy Survey shows that all sky surveys exhibit dipole axes well within 1$\sigma$ error from each other. While non-random distribution is unexpected, the findings are consistent across all sk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 211 publications
0
9
0
Order By: Relevance
“…As a model-driven method, it is not based on any kind of machine learning, and therefore it is not subjected to possible biases in the training data. Te simple "mechanical" nature of the Ganalyzer allows it to be fully symmetric [6,11].…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations
“…As a model-driven method, it is not based on any kind of machine learning, and therefore it is not subjected to possible biases in the training data. Te simple "mechanical" nature of the Ganalyzer allows it to be fully symmetric [6,11].…”
Section: Datamentioning
confidence: 99%
“…Previous work using diferent telescopes showed that the spin directions of spiral galaxies form a statistically significant large-scale axis [12]. Tat was carried out by ftting the spin directions to the cosine of the angle between the galaxies and every possible integer (α, δ) combination in the sky [11], as shown in the following equation:…”
Section: Identifcation Of a Possible Dipole Axis Alignmentmentioning
confidence: 99%
See 2 more Smart Citations
“…If so, thinking about the universe without a center of rotation is illogical. Based on this logic, we appeal the science community to see the possibility of thinking about angular velocity, cosmic rotation and rotational axis [38][39][40][41][42][43].…”
Section: On Cosmic Rotation and Cosmic Centermentioning
confidence: 99%